Background electrolytes influence on functioning of accumulative and indicator systems - Kozlova-Kozyrevskaya, Alla L.; Sankevich, Natal’ya A.; Mechkovskij, Stanislav A.; Molotok, Elena V. (Journal of the Belarusian State University. Chemistry, 2019)
The article considers the functioning features of the accumulative indicator systems associated with the nature and concentration of background electrolytes ions as well as the features caused by the process of exchange sorption of heavy metals in coacervate structure zones which are formed on zinc sulfide microparticles in the microscale affine chromatography mode. A comparative analysis of the use of aluminum oxide (A-SZ sorbent) and carboxymethylcelluloses (C-SZ) as carriers for active phase (ZnS) has been done. It is established that carboxymethylcellulose as a carrier has essential advantage. It was also demonstrated that the use of chloride, bromide and phosphate background solutions is more preferable than iodide. The results of this research may have practical interest, especially in production of cheap and easy test systems for environmental monitoring.
Keywords: microscale affinity chromatography; coacervate structures; interphase transfer effects; heavy metals; carriers for active phase